The impact of food packaging on consumer buying behavior / Syafafwati Zainuddin - Zainuddin, Syafafwati (2012)
The role of packaging has changed with the move to self-service retail formats and packaging performs an important role in marketing communications at the point of sales. Therefore, there is a necessity to explore packaging and its attributes in more details, in order to understand which of these attributes are the most important factors influencing the consumer’s purchase decision. This study is conducted in Malaysian context seek to reveal the impact of packaging attributes on consumer’s purchase decision of packaged food. A total of 100 consumers in Tesco Malacca were surveyed using a structured questionnaire. The results showed that packaging colors and technology are associated with purchase decision of packaged food products. Whereas, packaging graphics and printed information on packaged food do not have any significant relationship with purchase decision. The main implication for marketers is to recognize and take advantage on packaging as a strategic weapon and marketing tool to compete over their rivals.